2012
DOI: 10.1186/1472-6882-12-147
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from a double-blind randomised placebo-controlled study with a iota-carrageenan nasal spray as medical device in children with acute symptoms of common cold

Abstract: BackgroundCommon cold is caused by a variety of respiratory viruses. The prevalence in children is high, and it potentially contributes to significant morbidity. Iota-carragenan, a polymer derived from red seaweed, has reduced viral load in nasal secretions and alleviated symptoms in adults with common cold.MethodsWe have assessed the antiviral and therapeutic activity of a nasal spray containing iota-carrageenan in children with acute symptoms of common cold. A cohort of 153 children between 1–18 years (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(115 citation statements)
references
References 26 publications
5
101
1
1
Order By: Relevance
“…Carrageenans have shown antiviral activity against a number of viral pathogens, including HPV (43), HIV (44), dengue virus (45), and influenza A virus (46). Importantly, iota-carrageenan has been used safely in human trials in the form of a nasal spray to reduce viral infection (47)(48)(49).…”
Section: Iota-carrageenan Inhibits Hmpv Infection In Human Respiratormentioning
confidence: 99%
“…Carrageenans have shown antiviral activity against a number of viral pathogens, including HPV (43), HIV (44), dengue virus (45), and influenza A virus (46). Importantly, iota-carrageenan has been used safely in human trials in the form of a nasal spray to reduce viral infection (47)(48)(49).…”
Section: Iota-carrageenan Inhibits Hmpv Infection In Human Respiratormentioning
confidence: 99%
“…Between 2008 and 2011, three randomized clinical trials (two in adults and one in children) were conducted comparing I-C nasal spray with saline solution (placebo). In all 3 trials, there were indications of efficacy, including significantly reduced cold symptoms [5]; positive effects on symptoms in patients in whom less co-medication or no co-medication was used [6]; significantly reduced viral loads [5][6][7]; and faster reduction of common cold symptoms [6,7]. Treatments were safe and well tolerated [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that iota-carrageenan (a sulfated polysaccharide found in some species of red seaweed) exerts potent activity against respiratory viruses by directly binding to the infectious particles; however, carrageenan does not enter the host cell and is not expected to exert pharmacologic or immune activities [51]. Although iota-carrageenan was found to be effective as nasal spray in three clinical trials [1,51,52], it failed to achieve statistically significant outcomes for the primary and secondary endpoints in the most recent study [53]. Nasal irrigation with saline is often employed as an adjunct treatment for acute upper respiratory tract infections -particularly in children -and might relieve the symptoms to some extent [54].…”
Section: Discussionmentioning
confidence: 99%